Study on properties of hybrid reinforced composite using carbon fiber and kenaf fiber - Nurizzati, Idris (2017)
Hybrid composite has been developed and widely used in many industrial areas. The combination between the hybrid and composite lead to discovering of different and new varieties of properties which exceptionally not yet exist in nature. In this research, kenaf fiber and carbon fiber is being used by using hybridization process. The process of making kenaf-carbon fiber reinforced composite using resin transfer molding (RTM) technique.The resin transfer molding will inject the unsaturated polyester resin into the mold cavity then let the composite to cure and hardened completely. Experimental showed that the tensile and impact strength of kenaf-carbon fiber reinforced composite have high strength-to-weight ratio, increase in it ductility, more strong and stiff. Meanwhile, water absorption percentage shown that weight of kenaf-carbon fiber slightly increases which good resistance to water absorption. The surface morphology of were observed under scanning electron microscope shown the bonding of kenaf and carbon fiber and also matrix adhesion. Thermal gravimetric analysis discovered the higher weight loss percentage of kenaf-carbon reinforced composite due to kenaf fiber contain 45-57% of cellulose. Hence, hybridisation with carbon fiber showed an improvement in the properties of kenaf composite that suitable for industrial application.